2014
DOI: 10.1093/hmg/ddu267
|View full text |Cite
|
Sign up to set email alerts
|

Bardet–Biedl syndrome proteins 1 and 3 regulate the ciliary trafficking of polycystic kidney disease 1 protein

Abstract: Bardet-Biedl syndrome (BBS) and autosomal dominant polycystic kidney disease (ADPKD) are two genetically distinct ciliopathies but share common phenotypes such as renal cysts. Seven BBS proteins form a complex called the BBSome which is localized at the basal body or ciliary axoneme and regulates the ciliary entry or flagellar exit of several signaling molecules. Here, we demonstrate that, unlike the seven-span somatostatin receptor 3 or the leptin receptor that interacts with all subunits of the BBSome, the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 55 publications
(66 reference statements)
1
86
0
Order By: Relevance
“…In this context, polycystins and CDCA might not traffic sufficiently to cilia and thus generate a slow forming cystic phenotype. Interestingly PC1 is reported to interact with BBS1, BBS4, BBS5, and BBS8 and ciliary PC1 expression is reduced in BBS1 knockdown cells and BBS3 mutant cells (Su et al 2014). These findings support the possibility that relative PC1 deficiency may underlie a component of the cystic kidney phenotype in Bardet-Biedl syndrome.…”
Section: Cyst Formation In Other Ciliopathies In Relation To Pc1 -Pc2mentioning
confidence: 53%
“…In this context, polycystins and CDCA might not traffic sufficiently to cilia and thus generate a slow forming cystic phenotype. Interestingly PC1 is reported to interact with BBS1, BBS4, BBS5, and BBS8 and ciliary PC1 expression is reduced in BBS1 knockdown cells and BBS3 mutant cells (Su et al 2014). These findings support the possibility that relative PC1 deficiency may underlie a component of the cystic kidney phenotype in Bardet-Biedl syndrome.…”
Section: Cyst Formation In Other Ciliopathies In Relation To Pc1 -Pc2mentioning
confidence: 53%
“…PC1 and PC2 form a channel that localizes to the ciliary membrane and in the epithelium lining the renal tubules participate in sensing and transducing fluid flow shear stress into Ca 2+ signaling to control cell proliferation and differentiation [108]. Four members of the BBSome (BBS1, BBS4, BBS5 and BBS8) physically interact with PC1 but depletion of only BBS1 and BBS3 result in defective ciliary targeting of PC1, data that further supports the notion that different BBS proteins have specific functions [109]. In line with these observations, depletion of BBS7 does not affect the ciliary localization of PC1 and PC2 but affects that of dopamine D1 receptor [72].…”
Section: Renal Diseasementioning
confidence: 65%
“…65 Recently we found that PC1 interacts with several Bardet-Biedl syndrome (BBS) proteins that are part of the BBSome protein complex known to function in the transport of a set of proteins to the cilia. 66 Deficiency of BBS1 and BBS3 affects the ciliary trafficking of PC1. Hence, the polycystins are cargos of the BBSome and physical interactions between the polycystins and BBS proteins may underlie the overlapping renal phenotypes in these two diseases.…”
Section: Jing Zhoumentioning
confidence: 99%